1997
DOI: 10.1162/002081897550474
|View full text |Cite
|
Sign up to set email alerts
|

The Structuring of a World Environmental Regime, 1870–1990

Abstract: In recent decades a great expansion has occurred in world environmental organization, both governmental and nongovernmental, along with an explosion of worldwide discourse and communication about environmental problems. All of this constitutes a world environmental regime. Using the term regime a little more broadly than usual, we define world environmental regime as a partially integrated collection of world-level organizations, understandings, and assumptions that specify the relationship of human society to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
240
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(250 citation statements)
references
References 36 publications
2
240
0
8
Order By: Relevance
“…This increased interconnectedness has meant that interstate relations, national programmes and policies, and the circumstances of persons throughout the world have increasingly come under the scrutiny of a transnational web of regimes, international governmental and nongovernmental organisations and experts (Boli and Thomas, 1999;Finnemore, 1996;Meyer et al, 1997). Thus, this global institutional order, or world polity, is made up of strong and culturally empowered and legitimated actors who act through its network of influence, and operates as a constitutive and directive environment for states, business enterprises, groups, and individuals.…”
Section: Contextualising World Heritage -Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased interconnectedness has meant that interstate relations, national programmes and policies, and the circumstances of persons throughout the world have increasingly come under the scrutiny of a transnational web of regimes, international governmental and nongovernmental organisations and experts (Boli and Thomas, 1999;Finnemore, 1996;Meyer et al, 1997). Thus, this global institutional order, or world polity, is made up of strong and culturally empowered and legitimated actors who act through its network of influence, and operates as a constitutive and directive environment for states, business enterprises, groups, and individuals.…”
Section: Contextualising World Heritage -Theoretical Frameworkmentioning
confidence: 99%
“…The history of origins also illustrates the importance of scientific experts and expertise in such processes, and of having access to the international UN system (cf. Meyer et al, 1997), in this case UNESCO.…”
Section: The Convention -Events Perspectives and Structuresmentioning
confidence: 99%
“…It is "an institutionalist approach that explains the unexpectedly high and rising levels of isomorphism among states as a function of embeddedness in a singular and universalist 'world polity'" (Beckfield 2010(Beckfield : 1019. Through embeddedness in the world polity, it is argued, nation-states and other actors learn which actions are legitimate and which contrast with the world culture (Boli and Thomas 1997;Meyer et al 1997). For example, researchers have shown that nation-states with abundant ties to the world polity (through, for example, membership in international NGOs and intergovernmental organizations such as the IMF, World Bank, WTO, or the UN) prescribe environmental laws and regulations more rapidly than do less embedded nations (Frank 1999;Frank et al 2000;Schofer and Hironaka 2005).…”
Section: Literature Review: World-systems Analysis Of Development Andmentioning
confidence: 99%
“…In the third group of countries, appropriation seems to be more of an issue and the decoupling between global rules and local practices can be quite significant (Meyer et al 1997a, Meyer et al 1997b). In the case of the United States, geopolitical power allows for irregular and changing patterns of compliance even when that country has played a significant role in the process of elaboration of global rules (McNichol and Bensedrine 2003, ENS 2001, Libération 2002).…”
Section: 1mentioning
confidence: 99%